The Contribution of Abu'l-Muin an-Nasafî in the Spreading of Hanafi/Sunni Kalam in Transoxiana - SARIBULAK, Zekerya (Scientific Journal of Faculty of Theology, 2020)
Just after the region of Maveraunnehir joined to Islamic lands, Ebu Hanife's view about fikih and itikad reached that region by his students. Especially texts of akaids were moved to the region as written texts. Ecole scholars had made efforts in order to make sect remain in that region. But some scholars' efforts lead to make the sect remain in the region. The head of these scholars who made effort is Ebu'l-muin en Nesefi who is kalamist, commentator and fikih scholar. His debates with other religous groups caused to be systematized of the sect's kalam side with his works. Besides, the fact that the governments in that region had adhered to the sect of Hanefi accelerated that process.